Gravity constraint in cell phenotypic determination - Bizzarri, Mariano; Masiello, Maria Grazia; Cucina, Alessandra; Pensotti, Andrea (Organisms. Journal of Biological Sciences, 2017)
Distinct phenotypes emerge spontaneously when mammalian cells are cultured under microgravity conditions. Such finding is explained by the interplay among the intrinsic stochasticity, which, in turn, is successively ‘canalized’ and sustained by the activation of a specific gene regulatory network. However, when the two cell subsets are reseeded into a normal gravity field the two phenotypes collapse into one. Gravity constraints the system in adopting only one phenotype. Cell fate commitment is achieved through a de novo reshaping of the overall cell morphological and functional organization, and cannot be explained as a ‘selecting’ effect. Those findings highlight how constraints – acting as global order factors – drive cell specification and behavior. These data cast on doubt the current explanatory bottom-up, molecular based models.